Deterrent Effects of Antitrust Enforcement (United States): the Ready-Mix Concrete Industry, 1970-1980 - Block, Michael K. ([Verlag nicht ermittelbar], 1988)
These data were collected to explore the relationship between profit levels in the concrete industry and the antitrust enforcement activities undertaken by the United States Department of Justice in 19 cities over an 11-year period. The data collection is composed mainly of published aggregate data on ready-mix concrete costs and prices. Profits and estimates of collusive markups in this industry can be calculated and related to antitrust enforcement efforts. Variables include measures of wages and materials costs, prices of concrete products, number of building permits issued, gasoline prices, the consumer price index, number of laborers employed, unemployment rates, measures of change in the Department of Justice's Antitrust Division budget, change in number of DOJ permanent enforcement personnel, and number of antitrust criminal actions initiated by DOJ against ready-mix concrete users, producers of related products, producers of substitutes for ready-mix products, and ready-mix producers.